College Palliative Care Volunteers: Too Early to Feed the Pipeline for Palliative Care Clinicians? - Wu, Jennifer (J Palliat Med, 2019)
Background: The University of Iowa Hospitals and Clinics (UIHC) has a palliative care (PC) volunteering program that has recruited college students since 2010. There is little research on the effects of PC volunteering on collegiate volunteers. Objective: The objective is to determine the impact of PC volunteering on college students' professional lives and on their interest in PC. Design/Setting/Measurements: The UIHC Volunteer Services office sent a 25-question survey with closed- and open-ended items to previous and current PC college volunteers. We used descriptive statistics to characterize the sample. Free text responses were analyzed using a descriptive qualitative approach with three independent coders. Results: Seventy-one percent of respondents (23/33) reported they were more likely to pursue PC after volunteering. PC volunteering helped change views of patient care and abilities to discuss end-of-life situations. Ninety-one percent served as informal ambassadors by discussing PC with family and peers. Major themes identified include motivation to volunteer for patient contact and interest in learning about PC. Respondents described meaningful patient interactions, lessons in empathy, and the power of listening. Conclusions: These results suggest that PC volunteering affects career choices and helps volunteers gain needed listening skills for patient care in the future. The unique exposure and interactions with PC patients and their families have changed volunteers' understanding of health care. PC volunteers speak in their social networks about PC. This experience may increase the likelihood of student volunteers to pursue careers in PC.